(untitled) (Huellas, 2020)
Land suitability analysis based on Geographic Information Systems (GIS) is one of the most widely used applications for land planning. In this type of study, GIS and geospatial statistical tools are used to assess land units and to show the results in the form of aptitude maps. The present work aims at characterizing the suitability of the soils of the province of Catamarca for pecan nuts production based on 6 edaphic variables using GIS. The variables taken into account were rockiness, salinity, waterlogging risk, depth, texture and drainage. Soil Map of the Argentine Republic in 1: 500.000 scale published by the National Institute of Agricultural Technology was used as source. A classification of the aptitude of the soil cartographic units was made according to the crop requirements applying the methodology proposed by FAO. Omega score was applied for standardization of variables, and the spatial distribution of soil suitability was obtained by spatial classification score. The methodology applied allowed us to obtain the aptitude map based on the selected variables, resulting in a total of 60.662 km2 suitable for the production of pecan nuts, which represents 59.8% of the total surface of the province.